Experimental and numerical investigations of the flow around three different wall-mounted cylinder geometries of finite length - Uffinger, Thomas; Ali, Irfan; Becker, Stefan (Journal of Wind Engineering and Industrial Aerodynamics, 2013)
Three-dimensional flow fields around three different wall-mounted cylinder geometries of finite length are evaluated. A combined approach which uses both experimental and numerical investigations is applied to provide an extensive database. For the experimental investigations, laser Doppler anemometry is used to determine the averaged velocity vectors and the RMS values of the velocities. For the numerical investigations, three different simulation techniques are applied. A shear stress transport (SST) turbulence model represents RANS approaches. A hybrid simulation technique combining Reynolds-averaged Navier-Stokes (RANS) and large eddy simulation (LES) features is realized by the scale adaptive simulation (SAS) model. The third type of numerical simulation is LES, which is able to capture the unsteady flow field in the entire computation domain. Experimental and numerical results are presented and compared with each other. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.tech.ITC.stmmec.experi_8
Keywords: Laser Doppler anemometry; LES; SAS; SST; Wall-mounted square cylinder